Bridal Management System - Shairatulikram, Nurul Aishah; Ibrahim, Dr Noraini (Applied Information Technology And Computer Science, 2022)
Bridal Management System (BMS) is a system that able to give benefits to the bridal company that plan to have more systematic management. The system let the user to store the important data of the company. This system is developed due to problem statement collected from stakeholder. The problem that faced by the company is use of conventional method to keeping data likes customer details by using physical papers and files, waiting customer to booking an appointment, administrator having hard time to generate the report on customer booking. Thus, the objective from this project is to design bridal management system due to problem statement, to develop bridal management system and to test and evaluate the performance of the system. The methodology used to develop this project is a prototyping model. By this prototyping model, it enables to present the draft design for the client to get early figure on the system. Few phases that carried as a guide to develop this propose system. The system provided is web-based system. The language used is PHP web language from scratch. The database chosen for this proposed system is MySQL. The system proposed will consist of eight modules. The modules are register, login, manage inventory, booking appointment, manage booking, manage job, upload product and report. This system allows two users include the administrator and customer. The system able to let the administrator to manage the company data in better way. The customer of the bridal company able to book an appointment.